Going against mass tourism: Creative tourism as an alternative, creatour as an example - Gato, M. A. (2019)
In recent years, tourism statistics in Portugal have been showing a growth that is already beginning to cause some concern in the two major cities - Lisbon and Porto - while the rest of the country still expects to grow and benefit from this wave of tourist attractiveness that have been projecting the country in several international rankings. However, there is the notion that this growth should be done with some caution and in an adjusted manner, regarding the different territorial realities and in order to value the tangible and intangible assets that constitute tourism resources.For peripheral territories, such as rural areas or small sized cities, investing on creative tourism as a wide process of co-creation and exchange of cultural and symbolic experiences can be a good opportunity, not only to retain population and revitalize their cultural and social heritage, but also to enhance creative milieus and foster organic territorial dynamics, reflecting the “sense of place” and the unique characteristics of local communities.This communication will focus on cultural and creative tourism as a more sustainable and adapted alternative for low-density territories, giving the CREATOUR project as an example. This national multidisciplinary research project is being currently developed in the four NUTS II regions of Portugal. Simultaneously, CREATOUR works as an incubator of ideas and actions, aimed at providing the visitor-tourist co-production and knowledge experiences. Alongside with this creative tourism project and its conceptual bases, some of the results already obtained in the four regions of the country will also be presented and explored.